2021
DOI: 10.15503/emet2020.27.32
|View full text |Cite
|
Sign up to set email alerts
|

Advantages and disadvantages of distance learning

Abstract: Introduction. E-learning has been known and used in many countries for a long time.It is becoming more and more popular. It is a way of teaching remotely, using the latestinformation technology. It can be used in any age group, starting with pre-school teaching.In the era of the SARS-CoV-2 pandemic, remote learning has been mandatory due to theneed to continue the teaching process whilst at the same time reducing the risk of spreading the virus. This has revealed many advantages, but also the disadvantages of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 2 publications
0
9
0
3
Order By: Relevance
“…Klisowska et al also found that the excess of learning material is considered a disadvantage of distance education. 18 Hence, we identified that the abundance of reading material and problem sets may prevent the effectiveness of self-directed learning.…”
Section: Discussionmentioning
confidence: 99%
“…Klisowska et al also found that the excess of learning material is considered a disadvantage of distance education. 18 Hence, we identified that the abundance of reading material and problem sets may prevent the effectiveness of self-directed learning.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty of continuing to live in a rural community with few higher education options and with large commute distances to DE programmes, highlighted the challenges shared by participants with lack of distance education resources including internet availability, which would enable online engagements (Ali & Ahmaed, 2011;Arasaratnam-Smith & Northcote, 2017). Consequently, the lack of internet availability in rural areas further disadvantages these populations, and places rural folks at greater risk of educational deprivation and unmet educational needs (Brown, 2017;Sadeghi, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Öyle ki araştırmacıların tamamı uzaktan eğitimi; zamandan ve mekândan bağımsız bir şekilde eğitimin gerçekleşmesi olarak tanımlamaktadır. Ek olarak, bulgular göstermektedir ki öğrenciler uzaktan eğitimin, önceki araştırmalarda (Klisowska, 2021;Bouchikhi, 2021) Covid-19 salgını başlangıcından etkisinin devam ettiği süre boyunca Pamukkale Üniversitesi tarafından yürütülen uzaktan eğitim sistemine ilişkin turizm rehberliği bölümü öğrencilerinin algıları ve sürece yönelik memnuniyet düzeylerinin incelendiği bu çalışma sonunda birçok önemli sonuca ulaşılmıştır. Tüm bu sonuçların ışığında bazı öneriler geliştirilmiştir.…”
Section: Sonuç Tartişma Ve öNeri̇lerunclassified